2018
DOI: 10.3892/or.2018.6571
|View full text |Cite
|
Sign up to set email alerts
|

High expression of microRNA‑31 and its host gene LOC554202 predict favorable outcomes in patients with colorectal cancer treated with oxaliplatin

Abstract: The expression levels of microRNA‑31 (miR‑31) and LOC554202 have been previously investigated in colorectal cancer (CRC) and their oncogenic and/or tumor suppressive roles have been described. The aim of the present study was to examine the role of miR‑31 and its host gene LOC554202 in the prognosis of patients with CRC. Patients with CRC treated with oxaliplatin‑based chemotherapy between June 2005 and March 2010 were recruited to the First Affiliated Hospital of China Medical University. Tumor and adjacent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 54 publications
(76 reference statements)
0
21
1
Order By: Relevance
“…In CRC, the MIR31HG expression was negatively correlated with unfavorable prognosis, as indicated by advanced pathologic stage, and lager tumor size [19]. Consistently, Li Y et al found that high expression of MIR31HG predict high OS and DFS in CRC patients treated with oxaliplatin [32]. Given the prognostic significance of MIR31HG in cancers, in the current study, we firstly explored the association between MIR31HG level and clinical outcomes by performing a meta-analysis containing seventeen literatures with 2573 patients.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…In CRC, the MIR31HG expression was negatively correlated with unfavorable prognosis, as indicated by advanced pathologic stage, and lager tumor size [19]. Consistently, Li Y et al found that high expression of MIR31HG predict high OS and DFS in CRC patients treated with oxaliplatin [32]. Given the prognostic significance of MIR31HG in cancers, in the current study, we firstly explored the association between MIR31HG level and clinical outcomes by performing a meta-analysis containing seventeen literatures with 2573 patients.…”
Section: Discussionmentioning
confidence: 54%
“…Specifically, MIR31HG was found elevated expressed in breast cancer [13], cervical cancer [28], chordoma [16], osteosarcoma [15], lung cancer [2,23,41], OSCC [4], PDAC [7], VSCC [29] and LSCC [36,42,43]. Nevertheless, the expression levels of MIR31HG was reported down-regulated in triple-negative breast cancer (TNBC) cell lines of basal subtype [27], bladder cancer [26], gastric cancer [25], CRC [32,33], and HCC [6]. Besides, abnormal expression of MIR31HG was deemed as potential biomarker to reflect the clinicopathological characteristics and prognostic outcomes of cancer patients [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, another study revealed that MIR31HG appeared to have lower expression in ESCC tissues and patients with reduced MIR31HG were correlated with malignant clinical features. The contradictory expression patterns of MIR31HG were also found in breast cancer (13,27), CRC (19,32,33) and gastric cancer (25,34). In view of these conflicting data, for the first time, we performed this comprehensive metaanalysis of the current evidences in order to determine the predictive value of MIR31HG in various carcinomas.…”
Section: Introductionmentioning
confidence: 99%